72
|
1 {-# OPTIONS --allow-unsolved-metas #-}
|
|
2 module nat where
|
|
3
|
|
4 open import Data.Nat
|
|
5 open import Data.Nat.Properties
|
|
6 open import Data.Empty
|
|
7 open import Relation.Nullary
|
|
8 open import Relation.Binary.PropositionalEquality
|
|
9 open import Relation.Binary.Core
|
74
|
10 open import Relation.Binary.Definitions
|
72
|
11 open import logic
|
|
12
|
|
13
|
|
14 nat-<> : { x y : ℕ } → x < y → y < x → ⊥
|
|
15 nat-<> (s≤s x<y) (s≤s y<x) = nat-<> x<y y<x
|
|
16
|
|
17 nat-≤> : { x y : ℕ } → x ≤ y → y < x → ⊥
|
|
18 nat-≤> (s≤s x<y) (s≤s y<x) = nat-≤> x<y y<x
|
|
19
|
|
20 nat-<≡ : { x : ℕ } → x < x → ⊥
|
|
21 nat-<≡ (s≤s lt) = nat-<≡ lt
|
|
22
|
|
23 nat-≡< : { x y : ℕ } → x ≡ y → x < y → ⊥
|
|
24 nat-≡< refl lt = nat-<≡ lt
|
|
25
|
|
26 ¬a≤a : {la : ℕ} → suc la ≤ la → ⊥
|
|
27 ¬a≤a (s≤s lt) = ¬a≤a lt
|
|
28
|
|
29 a<sa : {la : ℕ} → la < suc la
|
|
30 a<sa {zero} = s≤s z≤n
|
|
31 a<sa {suc la} = s≤s a<sa
|
|
32
|
|
33 refl-≤s : {x : ℕ } → x ≤ suc x
|
|
34 refl-≤s {zero} = z≤n
|
|
35 refl-≤s {suc x} = s≤s (refl-≤s {x})
|
|
36
|
91
|
37 a≤sa : {x : ℕ } → x ≤ suc x
|
|
38 a≤sa {zero} = z≤n
|
|
39 a≤sa {suc x} = s≤s (a≤sa {x})
|
|
40
|
72
|
41 =→¬< : {x : ℕ } → ¬ ( x < x )
|
|
42 =→¬< {zero} ()
|
|
43 =→¬< {suc x} (s≤s lt) = =→¬< lt
|
|
44
|
|
45 >→¬< : {x y : ℕ } → (x < y ) → ¬ ( y < x )
|
|
46 >→¬< (s≤s x<y) (s≤s y<x) = >→¬< x<y y<x
|
|
47
|
|
48 <-∨ : { x y : ℕ } → x < suc y → ( (x ≡ y ) ∨ (x < y) )
|
|
49 <-∨ {zero} {zero} (s≤s z≤n) = case1 refl
|
|
50 <-∨ {zero} {suc y} (s≤s lt) = case2 (s≤s z≤n)
|
|
51 <-∨ {suc x} {zero} (s≤s ())
|
|
52 <-∨ {suc x} {suc y} (s≤s lt) with <-∨ {x} {y} lt
|
|
53 <-∨ {suc x} {suc y} (s≤s lt) | case1 eq = case1 (cong (λ k → suc k ) eq)
|
|
54 <-∨ {suc x} {suc y} (s≤s lt) | case2 lt1 = case2 (s≤s lt1)
|
|
55
|
210
|
56 n≤n : (n : ℕ) → n Data.Nat.≤ n
|
|
57 n≤n zero = z≤n
|
|
58 n≤n (suc n) = s≤s (n≤n n)
|
|
59
|
|
60 <→m≤n : {m n : ℕ} → m < n → m Data.Nat.≤ n
|
|
61 <→m≤n {zero} lt = z≤n
|
|
62 <→m≤n {suc m} {zero} ()
|
|
63 <→m≤n {suc m} {suc n} (s≤s lt) = s≤s (<→m≤n lt)
|
|
64
|
72
|
65 max : (x y : ℕ) → ℕ
|
|
66 max zero zero = zero
|
|
67 max zero (suc x) = (suc x)
|
|
68 max (suc x) zero = (suc x)
|
|
69 max (suc x) (suc y) = suc ( max x y )
|
|
70
|
|
71 -- _*_ : ℕ → ℕ → ℕ
|
|
72 -- _*_ zero _ = zero
|
|
73 -- _*_ (suc n) m = m + ( n * m )
|
|
74
|
|
75 exp : ℕ → ℕ → ℕ
|
|
76 exp _ zero = 1
|
|
77 exp n (suc m) = n * ( exp n m )
|
|
78
|
|
79 minus : (a b : ℕ ) → ℕ
|
|
80 minus a zero = a
|
|
81 minus zero (suc b) = zero
|
|
82 minus (suc a) (suc b) = minus a b
|
|
83
|
|
84 _-_ = minus
|
|
85
|
|
86 m+= : {i j m : ℕ } → m + i ≡ m + j → i ≡ j
|
|
87 m+= {i} {j} {zero} refl = refl
|
|
88 m+= {i} {j} {suc m} eq = m+= {i} {j} {m} ( cong (λ k → pred k ) eq )
|
|
89
|
|
90 +m= : {i j m : ℕ } → i + m ≡ j + m → i ≡ j
|
|
91 +m= {i} {j} {m} eq = m+= ( subst₂ (λ j k → j ≡ k ) (+-comm i _ ) (+-comm j _ ) eq )
|
|
92
|
|
93 less-1 : { n m : ℕ } → suc n < m → n < m
|
|
94 less-1 {zero} {suc (suc _)} (s≤s (s≤s z≤n)) = s≤s z≤n
|
|
95 less-1 {suc n} {suc m} (s≤s lt) = s≤s (less-1 {n} {m} lt)
|
|
96
|
|
97 sa=b→a<b : { n m : ℕ } → suc n ≡ m → n < m
|
|
98 sa=b→a<b {0} {suc zero} refl = s≤s z≤n
|
|
99 sa=b→a<b {suc n} {suc (suc n)} refl = s≤s (sa=b→a<b refl)
|
|
100
|
|
101 minus+n : {x y : ℕ } → suc x > y → minus x y + y ≡ x
|
|
102 minus+n {x} {zero} _ = trans (sym (+-comm zero _ )) refl
|
|
103 minus+n {zero} {suc y} (s≤s ())
|
|
104 minus+n {suc x} {suc y} (s≤s lt) = begin
|
|
105 minus (suc x) (suc y) + suc y
|
|
106 ≡⟨ +-comm _ (suc y) ⟩
|
|
107 suc y + minus x y
|
|
108 ≡⟨ cong ( λ k → suc k ) (
|
|
109 begin
|
|
110 y + minus x y
|
|
111 ≡⟨ +-comm y _ ⟩
|
|
112 minus x y + y
|
|
113 ≡⟨ minus+n {x} {y} lt ⟩
|
|
114 x
|
|
115 ∎
|
|
116 ) ⟩
|
|
117 suc x
|
|
118 ∎ where open ≡-Reasoning
|
|
119
|
|
120 sn-m=sn-m : {m n : ℕ } → m ≤ n → suc n - m ≡ suc ( n - m )
|
|
121 sn-m=sn-m {0} {n} z≤n = refl
|
|
122 sn-m=sn-m {suc m} {suc n} (s≤s m<n) = sn-m=sn-m m<n
|
|
123
|
|
124 si-sn=i-n : {i n : ℕ } → n < i → suc (i - suc n) ≡ (i - n)
|
|
125 si-sn=i-n {i} {n} n<i = begin
|
|
126 suc (i - suc n) ≡⟨ sym (sn-m=sn-m n<i ) ⟩
|
|
127 suc i - suc n ≡⟨⟩
|
|
128 i - n
|
|
129 ∎ where
|
|
130 open ≡-Reasoning
|
|
131
|
|
132 n-m<n : (n m : ℕ ) → n - m ≤ n
|
|
133 n-m<n zero zero = z≤n
|
|
134 n-m<n (suc n) zero = s≤s (n-m<n n zero)
|
|
135 n-m<n zero (suc m) = z≤n
|
|
136 n-m<n (suc n) (suc m) = ≤-trans (n-m<n n m ) refl-≤s
|
|
137
|
|
138 n-n-m=m : {m n : ℕ } → m ≤ n → m ≡ (n - (n - m))
|
|
139 n-n-m=m {0} {zero} z≤n = refl
|
|
140 n-n-m=m {0} {suc n} z≤n = n-n-m=m {0} {n} z≤n
|
|
141 n-n-m=m {suc m} {suc n} (s≤s m≤n) = sym ( begin
|
|
142 suc n - ( n - m ) ≡⟨ sn-m=sn-m (n-m<n n m) ⟩
|
|
143 suc (n - ( n - m )) ≡⟨ cong (λ k → suc k ) (sym (n-n-m=m m≤n)) ⟩
|
|
144 suc m
|
|
145 ∎ ) where
|
|
146 open ≡-Reasoning
|
|
147
|
|
148 0<s : {x : ℕ } → zero < suc x
|
|
149 0<s {_} = s≤s z≤n
|
|
150
|
|
151 <-minus-0 : {x y z : ℕ } → z + x < z + y → x < y
|
|
152 <-minus-0 {x} {suc _} {zero} lt = lt
|
|
153 <-minus-0 {x} {y} {suc z} (s≤s lt) = <-minus-0 {x} {y} {z} lt
|
|
154
|
|
155 <-minus : {x y z : ℕ } → x + z < y + z → x < y
|
|
156 <-minus {x} {y} {z} lt = <-minus-0 ( subst₂ ( λ j k → j < k ) (+-comm x _) (+-comm y _ ) lt )
|
|
157
|
|
158 x≤x+y : {z y : ℕ } → z ≤ z + y
|
|
159 x≤x+y {zero} {y} = z≤n
|
|
160 x≤x+y {suc z} {y} = s≤s (x≤x+y {z} {y})
|
|
161
|
|
162 <-plus : {x y z : ℕ } → x < y → x + z < y + z
|
|
163 <-plus {zero} {suc y} {z} (s≤s z≤n) = s≤s (subst (λ k → z ≤ k ) (+-comm z _ ) x≤x+y )
|
|
164 <-plus {suc x} {suc y} {z} (s≤s lt) = s≤s (<-plus {x} {y} {z} lt)
|
|
165
|
|
166 <-plus-0 : {x y z : ℕ } → x < y → z + x < z + y
|
|
167 <-plus-0 {x} {y} {z} lt = subst₂ (λ j k → j < k ) (+-comm _ z) (+-comm _ z) ( <-plus {x} {y} {z} lt )
|
|
168
|
|
169 ≤-plus : {x y z : ℕ } → x ≤ y → x + z ≤ y + z
|
|
170 ≤-plus {0} {y} {zero} z≤n = z≤n
|
|
171 ≤-plus {0} {y} {suc z} z≤n = subst (λ k → z < k ) (+-comm _ y ) x≤x+y
|
|
172 ≤-plus {suc x} {suc y} {z} (s≤s lt) = s≤s ( ≤-plus {x} {y} {z} lt )
|
|
173
|
|
174 ≤-plus-0 : {x y z : ℕ } → x ≤ y → z + x ≤ z + y
|
|
175 ≤-plus-0 {x} {y} {zero} lt = lt
|
|
176 ≤-plus-0 {x} {y} {suc z} lt = s≤s ( ≤-plus-0 {x} {y} {z} lt )
|
|
177
|
|
178 x+y<z→x<z : {x y z : ℕ } → x + y < z → x < z
|
|
179 x+y<z→x<z {zero} {y} {suc z} (s≤s lt1) = s≤s z≤n
|
|
180 x+y<z→x<z {suc x} {y} {suc z} (s≤s lt1) = s≤s ( x+y<z→x<z {x} {y} {z} lt1 )
|
|
181
|
|
182 *≤ : {x y z : ℕ } → x ≤ y → x * z ≤ y * z
|
|
183 *≤ lt = *-mono-≤ lt ≤-refl
|
|
184
|
|
185 *< : {x y z : ℕ } → x < y → x * suc z < y * suc z
|
|
186 *< {zero} {suc y} lt = s≤s z≤n
|
|
187 *< {suc x} {suc y} (s≤s lt) = <-plus-0 (*< lt)
|
|
188
|
|
189 <to<s : {x y : ℕ } → x < y → x < suc y
|
|
190 <to<s {zero} {suc y} (s≤s lt) = s≤s z≤n
|
|
191 <to<s {suc x} {suc y} (s≤s lt) = s≤s (<to<s {x} {y} lt)
|
|
192
|
|
193 <tos<s : {x y : ℕ } → x < y → suc x < suc y
|
|
194 <tos<s {zero} {suc y} (s≤s z≤n) = s≤s (s≤s z≤n)
|
|
195 <tos<s {suc x} {suc y} (s≤s lt) = s≤s (<tos<s {x} {y} lt)
|
|
196
|
|
197 ≤to< : {x y : ℕ } → x < y → x ≤ y
|
|
198 ≤to< {zero} {suc y} (s≤s z≤n) = z≤n
|
|
199 ≤to< {suc x} {suc y} (s≤s lt) = s≤s (≤to< {x} {y} lt)
|
|
200
|
|
201 x<y→≤ : {x y : ℕ } → x < y → x ≤ suc y
|
|
202 x<y→≤ {zero} {.(suc _)} (s≤s z≤n) = z≤n
|
|
203 x<y→≤ {suc x} {suc y} (s≤s lt) = s≤s (x<y→≤ {x} {y} lt)
|
|
204
|
|
205 open import Data.Product
|
|
206
|
|
207 minus<=0 : {x y : ℕ } → x ≤ y → minus x y ≡ 0
|
|
208 minus<=0 {0} {zero} z≤n = refl
|
|
209 minus<=0 {0} {suc y} z≤n = refl
|
|
210 minus<=0 {suc x} {suc y} (s≤s le) = minus<=0 {x} {y} le
|
|
211
|
|
212 minus>0 : {x y : ℕ } → x < y → 0 < minus y x
|
|
213 minus>0 {zero} {suc _} (s≤s z≤n) = s≤s z≤n
|
|
214 minus>0 {suc x} {suc y} (s≤s lt) = minus>0 {x} {y} lt
|
|
215
|
|
216 distr-minus-* : {x y z : ℕ } → (minus x y) * z ≡ minus (x * z) (y * z)
|
|
217 distr-minus-* {x} {zero} {z} = refl
|
|
218 distr-minus-* {x} {suc y} {z} with <-cmp x y
|
|
219 distr-minus-* {x} {suc y} {z} | tri< a ¬b ¬c = begin
|
|
220 minus x (suc y) * z
|
|
221 ≡⟨ cong (λ k → k * z ) (minus<=0 {x} {suc y} (x<y→≤ a)) ⟩
|
|
222 0 * z
|
|
223 ≡⟨ sym (minus<=0 {x * z} {z + y * z} le ) ⟩
|
|
224 minus (x * z) (z + y * z)
|
|
225 ∎ where
|
|
226 open ≡-Reasoning
|
|
227 le : x * z ≤ z + y * z
|
|
228 le = ≤-trans lemma (subst (λ k → y * z ≤ k ) (+-comm _ z ) (x≤x+y {y * z} {z} ) ) where
|
|
229 lemma : x * z ≤ y * z
|
|
230 lemma = *≤ {x} {y} {z} (≤to< a)
|
|
231 distr-minus-* {x} {suc y} {z} | tri≈ ¬a refl ¬c = begin
|
|
232 minus x (suc y) * z
|
|
233 ≡⟨ cong (λ k → k * z ) (minus<=0 {x} {suc y} refl-≤s ) ⟩
|
|
234 0 * z
|
|
235 ≡⟨ sym (minus<=0 {x * z} {z + y * z} (lt {x} {z} )) ⟩
|
|
236 minus (x * z) (z + y * z)
|
|
237 ∎ where
|
|
238 open ≡-Reasoning
|
|
239 lt : {x z : ℕ } → x * z ≤ z + x * z
|
|
240 lt {zero} {zero} = z≤n
|
|
241 lt {suc x} {zero} = lt {x} {zero}
|
|
242 lt {x} {suc z} = ≤-trans lemma refl-≤s where
|
|
243 lemma : x * suc z ≤ z + x * suc z
|
|
244 lemma = subst (λ k → x * suc z ≤ k ) (+-comm _ z) (x≤x+y {x * suc z} {z})
|
|
245 distr-minus-* {x} {suc y} {z} | tri> ¬a ¬b c = +m= {_} {_} {suc y * z} ( begin
|
|
246 minus x (suc y) * z + suc y * z
|
|
247 ≡⟨ sym (proj₂ *-distrib-+ z (minus x (suc y) ) _) ⟩
|
|
248 ( minus x (suc y) + suc y ) * z
|
|
249 ≡⟨ cong (λ k → k * z) (minus+n {x} {suc y} (s≤s c)) ⟩
|
|
250 x * z
|
|
251 ≡⟨ sym (minus+n {x * z} {suc y * z} (s≤s (lt c))) ⟩
|
|
252 minus (x * z) (suc y * z) + suc y * z
|
|
253 ∎ ) where
|
|
254 open ≡-Reasoning
|
|
255 lt : {x y z : ℕ } → suc y ≤ x → z + y * z ≤ x * z
|
|
256 lt {x} {y} {z} le = *≤ le
|
|
257
|
|
258 minus- : {x y z : ℕ } → suc x > z + y → minus (minus x y) z ≡ minus x (y + z)
|
|
259 minus- {x} {y} {z} gt = +m= {_} {_} {z} ( begin
|
|
260 minus (minus x y) z + z
|
|
261 ≡⟨ minus+n {_} {z} lemma ⟩
|
|
262 minus x y
|
|
263 ≡⟨ +m= {_} {_} {y} ( begin
|
|
264 minus x y + y
|
|
265 ≡⟨ minus+n {_} {y} lemma1 ⟩
|
|
266 x
|
|
267 ≡⟨ sym ( minus+n {_} {z + y} gt ) ⟩
|
|
268 minus x (z + y) + (z + y)
|
|
269 ≡⟨ sym ( +-assoc (minus x (z + y)) _ _ ) ⟩
|
|
270 minus x (z + y) + z + y
|
|
271 ∎ ) ⟩
|
|
272 minus x (z + y) + z
|
|
273 ≡⟨ cong (λ k → minus x k + z ) (+-comm _ y ) ⟩
|
|
274 minus x (y + z) + z
|
|
275 ∎ ) where
|
|
276 open ≡-Reasoning
|
|
277 lemma1 : suc x > y
|
|
278 lemma1 = x+y<z→x<z (subst (λ k → k < suc x ) (+-comm z _ ) gt )
|
|
279 lemma : suc (minus x y) > z
|
|
280 lemma = <-minus {_} {_} {y} ( subst ( λ x → z + y < suc x ) (sym (minus+n {x} {y} lemma1 )) gt )
|
|
281
|
|
282 minus-* : {M k n : ℕ } → n < k → minus k (suc n) * M ≡ minus (minus k n * M ) M
|
|
283 minus-* {zero} {k} {n} lt = begin
|
|
284 minus k (suc n) * zero
|
|
285 ≡⟨ *-comm (minus k (suc n)) zero ⟩
|
|
286 zero * minus k (suc n)
|
|
287 ≡⟨⟩
|
|
288 0 * minus k n
|
|
289 ≡⟨ *-comm 0 (minus k n) ⟩
|
|
290 minus (minus k n * 0 ) 0
|
|
291 ∎ where
|
|
292 open ≡-Reasoning
|
|
293 minus-* {suc m} {k} {n} lt with <-cmp k 1
|
|
294 minus-* {suc m} {.0} {zero} lt | tri< (s≤s z≤n) ¬b ¬c = refl
|
|
295 minus-* {suc m} {.0} {suc n} lt | tri< (s≤s z≤n) ¬b ¬c = refl
|
|
296 minus-* {suc zero} {.1} {zero} lt | tri≈ ¬a refl ¬c = refl
|
|
297 minus-* {suc (suc m)} {.1} {zero} lt | tri≈ ¬a refl ¬c = minus-* {suc m} {1} {zero} lt
|
|
298 minus-* {suc m} {.1} {suc n} (s≤s ()) | tri≈ ¬a refl ¬c
|
|
299 minus-* {suc m} {k} {n} lt | tri> ¬a ¬b c = begin
|
|
300 minus k (suc n) * M
|
|
301 ≡⟨ distr-minus-* {k} {suc n} {M} ⟩
|
|
302 minus (k * M ) ((suc n) * M)
|
|
303 ≡⟨⟩
|
|
304 minus (k * M ) (M + n * M )
|
|
305 ≡⟨ cong (λ x → minus (k * M) x) (+-comm M _ ) ⟩
|
|
306 minus (k * M ) ((n * M) + M )
|
|
307 ≡⟨ sym ( minus- {k * M} {n * M} (lemma lt) ) ⟩
|
|
308 minus (minus (k * M ) (n * M)) M
|
|
309 ≡⟨ cong (λ x → minus x M ) ( sym ( distr-minus-* {k} {n} )) ⟩
|
|
310 minus (minus k n * M ) M
|
|
311 ∎ where
|
|
312 M = suc m
|
|
313 lemma : {n k m : ℕ } → n < k → suc (k * suc m) > suc m + n * suc m
|
|
314 lemma {zero} {suc k} {m} (s≤s lt) = s≤s (s≤s (subst (λ x → x ≤ m + k * suc m) (+-comm 0 _ ) x≤x+y ))
|
|
315 lemma {suc n} {suc k} {m} lt = begin
|
|
316 suc (suc m + suc n * suc m)
|
|
317 ≡⟨⟩
|
|
318 suc ( suc (suc n) * suc m)
|
|
319 ≤⟨ ≤-plus-0 {_} {_} {1} (*≤ lt ) ⟩
|
|
320 suc (suc k * suc m)
|
|
321 ∎ where open ≤-Reasoning
|
|
322 open ≡-Reasoning
|
112
|
323
|
|
324 open import Data.List
|
|
325
|
|
326 ℕL-inject : {h h1 : ℕ } {x y : List ℕ } → h ∷ x ≡ h1 ∷ y → h ≡ h1
|
|
327 ℕL-inject refl = refl
|
|
328
|
|
329 ℕL-inject-t : {h h1 : ℕ } {x y : List ℕ } → h ∷ x ≡ h1 ∷ y → x ≡ y
|
|
330 ℕL-inject-t refl = refl
|
|
331
|
|
332 ℕL-eq? : (x y : List ℕ ) → Dec (x ≡ y )
|
|
333 ℕL-eq? [] [] = yes refl
|
|
334 ℕL-eq? [] (x ∷ y) = no (λ ())
|
|
335 ℕL-eq? (x ∷ x₁) [] = no (λ ())
|
|
336 ℕL-eq? (h ∷ x) (h1 ∷ y) with h ≟ h1 | ℕL-eq? x y
|
|
337 ... | yes y1 | yes y2 = yes ( cong₂ (λ j k → j ∷ k ) y1 y2 )
|
|
338 ... | yes y1 | no n = no (λ e → n (ℕL-inject-t e))
|
|
339 ... | no n | t = no (λ e → n (ℕL-inject e))
|
|
340
|